Diagnosis and management of malignant pleural effusions: state of the art in 2017 - Desai, Neeraj R.; Lee, Hans J. (Journal of Thoracic Disease; Vol 9, Supplement 10 (September 12, 2017): Journal of Thoracic Disease (Interventional Pulmonology), 2017)
Malignant pleural effusion (MPE) is a known complication of both thoracic and extra thoracic malignancies. The presence of MPE regardless of the primary site translates into advanced stage disease. Diagnosis and management of MPE with the goals of palliation and improving quality of life poses a challenge for chest physicians. Recently, multiple studies have made attempts to answer questions regarding optimal management in various clinical scenarios. We will review the current evidence and available options for the management of MPE.